2005
DOI: 10.1007/s10297-005-0054-0
|View full text |Cite
|
Sign up to set email alerts
|

Free-space laser communication performance in the atmospheric channel

Abstract: In spite of the tremendous technical advancement of available components, the major limitation of free-space laser communication (lasercom) performance is due to the atmosphere, because a portion of the atmospheric path always includes turbulence and multiple scattering effects. Starting from a fundamental understanding of the laser communications system under diverse weather conditions, this chapter provides a comprehensive treatment of the evaluation of parameters needed for analyzing system performance. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
119
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(130 citation statements)
references
References 37 publications
0
119
0
11
Order By: Relevance
“…So far, several atmospheric turbulence channel models have been proposed, of which log-normal and gamma-gamma models are the most commonly used for the cases of weak-to-moderate and moderate-to-strong turbulences, respectively. Previous works showed that they provided a good agreement between theoretical and experimental data [2,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…So far, several atmospheric turbulence channel models have been proposed, of which log-normal and gamma-gamma models are the most commonly used for the cases of weak-to-moderate and moderate-to-strong turbulences, respectively. Previous works showed that they provided a good agreement between theoretical and experimental data [2,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 60%
“…where s 2 s is the log intensity variance that depends on the channel's characteristics as given as [4,6] …”
Section: Channel Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…For weak to moderate atmospheric turbulence conditions, the turbulence-induced fading can be assumed as a random process that follows the lognormal distribution model which has the following probability density function (pdf) with respect to I [3,17],…”
Section: The Channel Modelmentioning
confidence: 99%
“…For an outdoor line-of-sight optical channel link, atmospheric turbulence represents an important capacity mitigation factor, in the sense that the received optical signal intensity fluctuates due to variation of the refractive index along the propagation path [3][4][5][6][7][8][9]. Hence, it is reasonable to expect that in a real FSO environment, optical channels will appear to have randomly time-varying characteristics.…”
Section: Introductionmentioning
confidence: 99%